UPAYA PENCEGAHAN STUNTING SEJAK PRA KONSEPSI MELALUI MODUL NKR_CATEN DAN KONSELING - TRIAWANTI TRIAWANTI; Didik Sanyoto; Fujiati Fujiati; Bambang Setiawan; Emmi Erliyanti; Siti juliati (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2020)
The prevalence of children under five with stunting in South Kalimantan in 2018 is 31%, under five underweight and very thin is 10.2%. In Banjar district the number of free malnutrition is only 31.5%. Factors affecting nutrition problems in infants and toddlers include physical condition, age and mother's knowledge. Nutritional status and good nutritional intake in pre-pregnancy also determine and this can be anticipated earlier. The prospective bride (CATEN) is the right target in preventing nutritional problems. The purpose of this activity is to increase the knowledge of the prospective bride about reproductive health, nutrition, and development of babies. The methods of this activity are 1) making the NKR_CATEN module; 2) module printing; 3) distributing modules as well as providing counseling and counseling to prospective brides; and 4) Evaluation. The partner of the activity is the Office of Religious Affairs (KUA), West Martapura District. The results show that the age of the prospective bride who is involved in this activity is an average of over 20 years old and education at the high school and university level is 50%. This is a good asset for caten to be able to provide care for their children. After giving the NKR_CATEN module and counseling to the prospective bride can be seen in the increase in knowledge of the prospective bride at the posttest. The mean value obtained is higher than the pretest. Conclusion: providing the NKR-CATEN module can increase the knowledge of the prospective bride and groom about nutrition and reproductive health.